Pathways of Organic Carbon Downward Transport by the Oceanic Biological Carbon Pump - Le Moigne, Frédéric A. C. (Frontiers in Marine Science, 2019)
The oceanic biological carbon pump (BCP) regulates the Earth carbon cycle by transporting part of the photosynthetically fixed CO2 into the deep ocean. Suppressing this mechanism would result in an important increase of atmospheric CO2 level. The BCP occurs mainly in the form of (1) organic carbon (OC) particles sinking out the surface ocean, of (2) neutrally buoyant OC (dissolved or particulate) entrained by downward water masses movements and/or mixing, and of (3) active transport of OC by migrating animals such as zooplankton and fishes. These various pools of OC differ in size since their sinking, production and decomposition rates vary spatially and temporally. Moreover, the OC transported to depths via these various export pathways as well as their decomposition pathways all have different ecological origins and therefore may response differently to climate changes. Currently, most ocean biogeochemical models do not resolve these various of OC pathways explicitly; rather, they imply that OC is therein created and destroyed equally. In addition, the organic composition of these various pools is largely unknown, especially at depths below 500 m. Here, known processes of OC export from the surface ocean to the mesopelagic zone (100–1000 m) are briefly reviewed. Three OC export pathways and some of their sub-categories are considered. I refer to published studies of OC fluxes associated with the specific downward export pathways and identify gaps that need to be addressed to better understand the OC fluxes associated with the BCP.